n = 1 ∑ ∞ ∫ 0 1 n 2 x n − 1 ln 2 ( x ) ln ( 1 − x ) d x = − b π a
Find a + b for the following problem
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Huh! This is it? It is so stupid of me! I took that integral as derivatives of Beta function and solved it.
Log in to reply
Hahaha.. Use short method :D
Log in to reply
This didn't strike me at all!
Log in to reply
@Aditya Kumar – no problem dude your method is also good...
How did u get 6 in the denominator plz explain.
You skipped a lot of steps from the third last line to the second last line.
Problem Loading...
Note Loading...
Set Loading...
Rewrite the Integral by expressing lo g ( 1 − x ) = − ∑ m = 1 ∞ m x m
Therefore , after rearranging terms we get
= − n = 1 ∑ ∞ m = 1 ∑ ∞ 0 ∫ 1 m n 2 x m + n − 1 lo g 2 x d x
= − n = 1 ∑ ∞ m = 1 ∑ ∞ ( m + n ) 3 m n 2 2
= − 2 × 6 ζ ( 6 )
= − 2 8 3 5 π 6